Evaluación de los métodos de mitigación de brotes de bacteriosis en el cultivo de banano. - Mendoza Marin, Andres Alejandro; Gomez Lazo, Javier Andres (Machala : Universidad Técnica de Machala, 2025)
This descriptive research with an experimental design was conducted on a banana farm located in El Guabo canton, El Oro province (Ecuador), with the objective of evaluating the effectiveness of three mitigation methods applied to plants infected with Ralstonia solanacearum Race 2, the causal agent of Moko disease in bananas. Initially, plants with compatible symptoms were identified through phytosanitary field inspection, and tissue was extracted from the pseudostem. Subsequently, bacterial isolation was performed in the laboratory using the TTC selective medium (triphenyl tetrazolium chloride), which allowed confirmation of the pathogen's presence through the analysis of characteristic pigmented colonies. Once the infected plants were diagnosed, three different treatments were applied: (1) chopping the plant and applying 5 kg of agricultural lime with a soil cover, (2) chopping and placing the biomass in a plastic bag with the application of urea in a 1:1 ratio relative to the fresh weight of the biomass, and (3) direct injection of glyphosate into the pseudostem. A field follow-up was carried out within a 100-meter radius in each case to identify potential spread of the infection focus. The results showed that the method based on urea was the most effective, as no new infected plants were detected. The glyphosate treatment showed intermediate effectiveness, with one symptomatic plant found, while the agricultural lime method was less effective, with two new infected plants identified. These findings support the use of urea as an effective strategy to contain localized outbreaks of bacterial wilt in musaceae under tropical conditions.
La presente investigación es de carácter descriptivo con diseño experimental, se desarrolló en una finca bananera del cantón El Guabo, provincia de El Oro (Ecuador), con el objetivo de evaluar la eficacia de tres métodos de mitigación aplicados a plantas infectadas por Ralstonia solanacearum raza 2, agente causal del Moko del banano. Inicialmente, se identificaron plantas con sintomatología compatible mediante inspección fitosanitaria en campo extrayendo tejido del pseudotallo. Posteriormente, se realizó el aislamiento bacteriano en laboratorio utilizando el medio selectivo TTC (trifenil tetrazolio cloruro), que permitió confirmar la presencia del patógeno mediante el análisis de colonias pigmentadas características. Una vez diagnosticadas las plantas enfermas, se aplicaron tres tratamientos distintos: (1) troceado de la planta con aplicación de cal agrícola (5 kg) y cobertura con suelo, (2) troceado e incorporación en bolsa plástica con aplicación de urea en proporción 1:1 respecto al peso fresco de la biomasa, y (3) inyección directa de glifosato en el pseudotallo. Se realizó un seguimiento en campo dentro de un radio de 100 metros para cada caso, con el fin de identificar la posible expansión del foco de infección. Los resultados mostraron que el método basado en urea fue el más eficaz, ya que no se detectaron nuevas plantas infectadas. El tratamiento con glifosato tuvo efectividad intermedia al encontrarse una planta con síntomas, mientras que el método con cal agrícola resultó menos eficiente, con dos plantas nuevas afectadas. Estos hallazgos respaldan el uso de urea como estrategia efectiva para contener brotes localizados de bacteriosis en musáceas bajo condiciones tropicales.
Keywords: MITIGACIÓN; RALSTONIA SOLANACEARUM; BACTERIOSIS; TTC